Dynamics of mountain urbanisation: evidence from the trans-himalayan town of Kargil, Ladakh, India - Hussain, Altaf; Schmidt, Susanne; Nüsser, Marcus (Land, 2023)
Small and medium-sized towns in the high mountain regions of South Asia are characterised by rapid and mostly unplanned urbanisation processes, regularly resulting in an increased risk of urban agglomerations being exposed to natural hazards. After the administrative capital of Leh, Kargil town is the second-largest urban centre in the Union Territory (UT) of Ladakh. This article discusses the development and dynamics of the Trans-Himalayan town in terms of its historical development, expansion and population; land use and land cover (LULC) change; and the specific role of tourism. Based on a multi-temporal approach using high-resolution satellite images, statistical data and field surveys, the urban landscape dynamics of Kargil town are analysed. The total population of this town increased almost tenfold from 1681 in 1961 to 16,338 in 2011, which resulted in an increase in the urban population from 3.7% to 11.6%, while the population of the entire Kargil district only tripled from 45,064 to 140,802 over the same period. Migration from rural villages to Kargil town has been a major cause for the construction and growth of new residential colonies and settlements. The built-up area increased more than ninefold from 0.25 km2 (1.3%) to 2.30 km2 (11.7%) between 1965 and 2020. During the same period, irrigated land and hygrophilous vegetation increased considerably from 4.51 km2 (23.0%) to 8.56 km2 (43.6%) due to the construction of new water channels. Similarly, the barren area decreased significantly from 14.88 km2 (75.8%) to 8.78 km2 (44.7%) between 1965 and 2020. Moreover, the massive increase in tourist arrivals has led to the construction of more hotels, guesthouses and travel agencies. These key factors play a significant role in the emergence, growth and development of this high-mountain town.
Gesehen am 07.06.2023